Applicability of economic models in estimating tourism impacts - Chia, Kei Wei; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Education and Novel Technology Research Association, 2013)
In many countries, tourism is perceived as a tool to generate income and employment to a country and local economy. Therefore, many researchers attempt to estimate the economic impacts of tourism through different kind of methods. Economic impact studies can be carried out using primary or secondary data. However, there is no universally accepted model to estimate the economic impact because different models give different results based on the interest of the researchers. The objective of this paper is to discuss the strengths, weaknesses, and the applicability of four commonly techniques used in estimating economic impacts of tourism: Input-output model, Social Accounting Matrix, Computable General Equilibrium, and Tourism Satellite Account. Subsequently, the justification of choosing an appropriate model in estimating the economic impacts of tourism is discussed.